Learning strategies in the communication área In reading comprehension. Case.- first grade students of secondary of the educational institution N° 3069 "Generalísimo José de San Martin" - Ancón - Lima 2020 - Cano Valdivia, Giovana Teresa (2021)
This scientific study is basic, correlational, not experimental. Study factors: the learning strategies of the Communication area in the reading comprehension of the in first grade high school students of the Educational Institution N ° 3069 "Generalissimo José de San Martin" - Ancón - Lima 2020. The instruments meet the qualities of validity and reliability. The study raises the following research hypothesis: There is a difference between the control group and the experimental group in the post test, when applying the learning strategies of the area of Communication in the reading comprehension of the in students of first grade of secondary school. Educational Institution N ° 3069 "Generalissimo José de San Martin" - Ancón - Lima 2020. The results obtained, through descriptive and inferential statistical techniques, allow rejecting the null hypothesis and accepting the alternative hypothesis, accepting that the learning strategies in the area of Communication improve the reading comprehension of the first-grade students of the Educational Institution No. 3069 “Generalissimo José de San Martin” - Ancón - Lima 2020 when obtaining that the p value = 0.000 <0.05